Acetabular reconstruction in oncological surgery: A systematic review and meta-analysis of implant survivorship and patient outcomes. (September 2021) - Kostakos, Thomas A.; Nayar, Sandeep Krishan; Alcock, Harry; Savvidou, Olga; Vlasis, Konstantinos; Papagelopoulos, Panayiotis J.
Abstract: Background: Reconstruction of the hip for peri-acetabular oncological disease remains a challenge. The objective of this study was to summarize the evidence and identify techniques utilized for primary and metastatic tumors of the acetabulum and hemipelvis. Methods: A systematic review of the published literature was carried out in accordance with PRISMA guidelines. MEDLINE, EMBASE and Cochrane databases identified relevant articles. Quality was assessed using the Newcastle-Ottawa Scale. The study was registered on PROSPERO. Results: 53 papers were included, 16 were suitable for meta-analysis. 909 patients had primary and 1140 metastatic disease. 1094 patients underwent reconstruction with conventional total hip arthroplasty (with or without cup-cage or cement augmentation) or modifications of the Harrington procedure, collectively termed 'non-complex'. 928 patients underwent 'complex' reconstructions with either a modular hemipelvic, saddle, reverse snow-cone, custom-made or 3D-printed endoprosthesis. The most common complication was deep infection (11%) followed by dislocation (5%). Mean MSTS scores were 61.9% for 'non-complex' versus 63.2% for 'complex' reconstruction. Meta-analysis suggested increased mortality for primary (OR 3.14; 95% CI 1.15–8.54) and trends toward reduced mortality for metastatic disease (OR 0.93; 95% CI 0.26–3.29) following 'complex' versus 'non-complex' reconstruction. Reoperation rates were higher following 'complex' reconstruction for metastatic disease (OR 1.90; 95% CI 0.66–5.46) and similar for primary disease (OR 0.98; 95% CI 0.45–2.14). Conclusions: Peri-acetabular tumors are associated with high rates of morbidity and mortality. Decisions regarding implant selection are multi-factorial with recent increase in the use of custom-made and 3D-printing technologies. Multiple factors contribute to the oncological outcome and patient function. Further research is required in order to guide optimal practice. Highlights: ● Peri-acetabular tumors are associated with high rates of morbidity and mortality ● Multiple reconstructive options for primary and metastatic periacetabular tumors ● Custom and 3D-printing technology has increased in recent years ● Trend towards lower mortality for metastatic disease using custom implants ● Rapidly developing field in Orthopedic Oncology